The Cambridge companion to Mario Vargas Llosa - Kristal, Efraín; King, John (Cambridge ; New York : Cambridge University Press, 2012)
"One of the major novelists in world literature over the last five decades, Mario Vargas Llosa (b. 1936) is also one of Latin America's most engaging public intellectuals, a critic of art and culture, and a playwright of distinction. This Companion's chapters chart the development of Vargas Llosa's writings from his rise to prominence in the early sixties to the award of the Nobel Prize for Literature in 2010. The volume traces the development of his literary trajectory, and the ways in which he has reinvented himself as a writer. His vast output of narrative fiction is the main focus, but the connections between his concerns as a creative writer and his rich career as a cultural and political figure are also teased out in this engaging, informative book"--Provided by publisher.
Chronology -- Introduction / Efrain Kristal and John King -- Reality, rebellion, and the paradox of power. An overview of Mario Vargas Llosa's literary themes / Alonso Cueto -- The early novels. The time of the hero and The green house / Gerald Martin -- The total novel and the novella. Conversation in the cathedral and the cubs / Efrain Kristal -- Humour and irony. Captain Pantoja and the special service and Aunt Julia and the scriptwriter / Michael Wood -- The historical novel. The war of the end of the world / Juan E. de Castro and Nicholas Birns -- Innocence and corruption. Who killed Palomino Molero? and The storyteller / Fiona Mackintosh -- The political novels. The real life of Alejandro Mayta and Death in the Andes / Deborah Cohn -- The erotic novels. In praise of the stepmother and The notebooks of Don Rigoberto / Roy C. Boland -- The dictator novel The feast of the goat / Clive Griffin -- From utopia to reconciliation. The way to paradise, The bad girl, and 'The dream of the celt' / Efrain Kristal -- The essays / John King -- The memoir / Kelly Austin -- The plays / Evelyn Fishburn -- Film and the novels / Carolina Sitnisky -- The interview / Efrain Kristal and John King with Mario Vargas Llosa .
Bibliografija. - Kazala
Keywords: Vargas Llosa, Mario, -- 1936- -- Criticism and interpretation; Vargas Llosa, Mario, -- 1936- -- Political activity; Vargas Llosa, Mario, -- 1936- -- Influence; Vargas Llosa, Mario